Determination method of the cavern boundary viscosity in a stirred tank with pseudoplastic fluid. Issue 5 (14th February 2020) - Luan, Deyu; Wang, Zhaorui; Wang, Hong; Wang, Songsong; Li, Longbin; Chen, Yiming
Abstract: It is essential to predict the cavern boundary accurately for investigating the cavern characteristics and achieving efficient mixing of the pseudoplastic fluids. The distribution characteristics of apparent viscosity of xanthan gum solutions at different mass concentrations stirred by the impeller of perturbed six‐bent‐bladed turbine (6PBT impeller) were numerically investigated through the computational fluid dynamics (CFD) simulation based on laminar flow model. The determination method of the cavern boundary viscosity was presented, and the predicted results were compared with those of traditional velocity method. Results showed that the data of the power consumption predicted using CFD simulation agreed well with those measured by torque experiment, which validated the laminar flow model. The η a  −  γ curve changes from nearly horizontal straight line to the power function curve along the direction of center axis toward tank wall. As a result, the location of the transitional point can be determined as the cavern boundary, and the corresponding viscosity is the cavern boundary viscosity. The ratio of the cavern boundary viscosity and the fluid yield viscosity ( η a / η y ) always remains approximately constant, that is, η ¯ a = 0.25 η y at different speeds. Compared with the traditional velocity method, the boundary viscosity method can maintain its high accuracy for exhibiting the cavern boundary, and the predicted cavern size and development are always in good agreement with the CFD results free from the speed and the impeller type. So this work can provide a new way for accurately characterizing the cavern boundary.